Stereoselective preparation of P, axial-stereogenic allenyl bisphosphine oxides via chirality-transfer. Issue 16 (1st April 2020) - Qiu, Mao-Ran; Zheng, Hong-Xing; Ye, Jing-Jing; Yan, Bing-Xia; Zhao, Chang-Qiu; Li, Qiang
Abstract : Allenyl bisphosphine oxides having variable chirality were prepared in high dr, which was controlled by chiral carbon and phorphorus. Abstract : P, C -Stereogenic propargyl alcohols R C -3 / S C -3′ were prepared by the addition of ( L )-menthyl-derived SPOs to propynals, which were converted to P, axial -stereogenic allenyl bisphosphine oxides. The chirality transfer was controlled by α-carbon via syn [2, 3]-sigmatropic rearrangement. For S C -3′ linking weak WDG on the alkynyl moiety, the chirality on the axis depended on stereogenic phosphorus.